ENHANCING STUDENTS’ SPEAKING ABILITY BY APPLYING THINK-PAIR SHARE TECHNIQUE FOR THE STUDENTS OF XII IPS 4 MA NEGERI I BOJONEGORO IN THE ACADEMIC YEAR OF 2016/2017 - Nadif Ulfia (IKIP PGRI Bojonegoro, 2017)
Abstract: Enhancing Students’ Speaking Ability by Applying Think-Pair Share Technique for the Students of XII IPS 4 MA Negeri I Bojonegoro in the Academic Year of 2016/2017. In fact, many students have difficulties in communicating in English. The writer proposes using Think-Pair-Share (TPS) learning technique which can be considered as an alternative. The result of the preliminary study shows that the students speaking ability was very low, the average score was only 6.3 which was much lower than stated passing grade score, that is 7.5. There were only 9 out of 32 students who were actively involved in the speaking activity. This research is conducted in order to find out whether using Think-Pair-Share technique enables the students to participate actively in speaking class. The study carried out by applying Classroom Action Research. The selecting subjects were the XII IPS 4 students in the academic year 2016/2017. The data collection involves a number of instruments are: a preliminary study, a questionnaire and an observation sheets. The result shows that there were some improvement of active students (6.87). The result of cycle 2 shows that there were 28 out of 32 students who actively participated in the speaking activity. The mean score of the students speaking ability could reach 7.56. Based on the data it can be said that the action in cycle 2 brought a success that TPS technique is effective to enhance the students’ speaking ability.Keywords: Teaching Technique, Think-Pair Share, Speaking,Abstrak: Meningkatkan Kemampuan Berbicara dengan Penerapan Teknik Think-Pair Share pada Siswa Kelas XII IPS 4 MA Negeri 1 Bojonegoro pada Tahun Pelajaran 2016/2017. Pada kenyatannya, banyak siswa mengalami kesulitan dalam berkomunikasi dalam Bahasa Inggris. Penulis menyarankah untuk menggunakan teknik mengajar Think-Pair Share (TPS) yang dapat dijadikan sebagai alternatif. Hasil studi pendahuluan menunjukkan bahwa kemampuan para siswa dalam berbicara menggunakan Bahasa Inggris sangatlah rendah. Nilai rata-rata siswa hanya pada level 6.3 dibawah kkm yang ditetapkan, yaitu 7.5. Hanya terdapat 9 dari 32 siswa yang secara aktif terlibat dalam berkomunikasi dalam Bahasa inggris. penelitian ini dilakukan untuk mengetahui apakah dengan menggunakan teknik TPS mampu membuat para siswa berpartisipasi secara aktif di kelas. Penelitian ini adalah Penelitian Tindakan Kelas. Subyek penelitian ini adalah parasiswa kelas XII IPS 4 pada tahun akademik 2016/2017. Pengumpulan data dilakukan melalui pre-tes, kuesioner, dan lembar observasi. Hasil penelitian menunjukkan bahwa terdapat beberapa peningkatan junlah siswa yang aktif berpartisipasi dikelas (6.87%) pada siklus 1 ang masih harus ditingkatkan pada siklus 2. Hasil peneitian pada siklus 2 menunjukkan bahwa terdapat 28 dari 32 siswa yang turut aktif baerpartisispasi dikelas (7.56). Berdasarkan hasil penelitian dapatdisimpulkan bahwa aktivitas pada siklus 2 berhasil membwa kesuksesan untuk meningkatkan kemampuan siswa berbicara.Kata kunci: teknik mengajara, Think-pair Share, berbicara.